Seismic retrofitting solution of an adobe masonry wall - Figueiredo, A.
Adobe constructions represent a high percentage of the national patrimony, with high historical, cultural and architectonic value. Well preserved adobe structures can exhibit a particular architecture with very attractive geometric characteristics while also incorporating natural materials. However, the behavior of these structures is deficient under horizontal loads, such as those induced by an earthquake, which endangers their structural integrity and human lives. To develop a seismic retrofit solution, a real-scale wall was characterized and tested by considering permanent vertical actions with cyclic horizontal forces of increasing amplitude. To retrofit the wall, repair and seismic reinforcement solutions were developed and combined to evaluate their efficiencies. To repair the damages, hydraulic lime gum was injected by pressure into the cracks. The reinforcement solution included the use of a synthetic mesh in the wall. The retrofitted wall was then tested, and the results indicated that the retrofit solutions significantly improved the seismic performance of the wall. This study contributes to the characterization of walls constructed with adobe masonry and their behavior under horizontal actions. Furthermore, an economic, sustainable and efficient solution is presented for the retrofitting of adobe walls, with significant performance improvements obtained.